Methylation sites of human papillomavirus 16 as potential biomarkers for cervical cancer progression - Ji, Sha; Ji, Nannan (Frontiers in Oncology, 2025)
ObjectiveTo investigate the methylation levels at 13 specific sites of the human papillomavirus 16 (HPV16) L1 gene as potential biomarkers for the diagnosis of cervical cancer.MethodsSamples were collected from the gynecological outpatient and inpatient departments of the Xinjiang Uygur Autonomous Region People’s Hospital. A total of 107 women participated in this study, including 54 with cervical cancer (32 Uygur, 22 Han) and 53 with cervical inflammation (32 Uygur, 21 Han). Methylation analysis was performed using pyrosequencing to quantitatively assess methylation levels at specified CpG sites within the HPV16 L1 gene.ResultsHigh methylation levels were predominantly observed at sites 5927, 5963 and 6367 in cervical cancer cells compared with inflammatory cells. Methylation patterns exhibited no significant differences between the Han and Uygur ethnic groups but correlated with viral load and age within each group. Receiver operating characteristic curve analyses of these methylation sites indicated high diagnostic accuracy in distinguishing between high-grade lesions and less severe conditions.ConclusionsMethylation of specific CpG sites in the HPV16 L1 gene holds promise as a biomarker for cervical cancer progression. The gene locus at position 6367 has important features in the methylation pattern of cervical cancer, and high accuracy shown in diagnosis make it a potential biomarker for early diagnosis of cervical cancer.